Efeitos renais e pulmonares do veneno da cascavel (Crotalus durissus cascavella) em ratos: estudo epidemiológico dos acidentes ofídicos no Ceará - Feitosa, Regina Fátima Gonçalves (1996)
Ophidian accidents are a severe public health problem in the tropics. Seven sub-species of Crotalus durissus are distributed in different regions of Brazil, and among these sub-species a major interest for the present study is focused on Crotalus durissus cascavella, mostly found in Northeastem Brazil. We aimed, in this work, at analysing the effects of Crotalus durissus cascavella venom on the kidney and lung of the rat, through a histological analysis of these organs and dosages of same serum parameters related to the kidney function, as well as to analyze epidemiological aspects of the ophidian accidents in Ceará between 1992 and 1995. The method of probits (Miller & Tainter, 1944) was used to calculate the lethal dosis. The DL50 for the venom of C. d. cascavella was observed to be that of 3.0 ± 0.34 mg/kg. Hundred and forty wistar rats, weighing 140-200g, distributed in control (n=4) and experimental (n=5 ou 6) groups inoculated intraperitoneally with 3mg/kg of venom were used. The animais were killed in different time intervals (6h, 12h, 24h, 2 days, 4d, 15d, 21 d e 28d) and blood was collected when the animais were decapited. In each time interval a control (C) and an experimental group (E) was killed. Kidneys were removed and colored by hematoxyline-eosine (HE), PAS, thrichrom of Masson, and silver metenamina for optic microscopy analysis. Among 56 animais dead by the venom 14 of them were autopsied the kidneys and lungs fforn these animais were colored by HE and analysed by optic mycroscopy. In this study, a significant reduction was detected in the serum leveis of total proteins and globulin in the experimental group of 12h (Ci2h=6.5 ± 0.22g/dl; Ei2h=5.63 ± 0.26g/dl* for total proteins and Ci2h=3.5 ± 0.23g/dl; Ei2h=2.77 ± 0.18g/dl* for globulin) and a significant reduction in the serum albumin in the experimental groups of 2 days and 4 days (C2d=3.33 ± O.88g/dl; E2d=2.9 ± 0.03g/dl* and C4d=3.45 ± 0.07g/dl; E4d=3.14 ± O.lg/dl*). A significant reduction of Na+ was also observed in the group experimental of 2d (C2d=l 42.25 ± 2.25mEq/l; E2d=131.8 ± 0.92mEq/l*). In the group of 15d, there was an increase of creatinine (Ci5d=0.57 ± 0.02mg/dl; Ei5d=0.77 ± 0.04mg/dl*).*p<0.05. The histological analysis of the kidneys showed a vascular congestion in intersticial and glomerular capillary loops, predominant in intensity and number in the animais dead by the venom and in the experimental group of 6h.